Multifunctional CNT‐Polymer Composites for Ultra‐Tough Structural Supercapacitors and Desalination Devices. (23rd August 2013) - Benson, Jim; Kovalenko, Igor; Boukhalfa, Sofiane; Lashmore, David; Sanghadasa, Mohan; Yushin, Gleb
<x xml:space="preserve">Abstract</x> Pulsed electrodeposition of polyaniline (PANI) allows the fabrication of flexible, electrically conductive, nonwoven PANI‐carbon nanotube (PANI‐CNT) composite fabrics. They possess specific tensile strength and a modulus of toughness higher than that of aluminum matrix composites, titanium and aluminum alloys, steels, and many other structural materials. Electrochemical tests show that these nanocomposites additionally offer excellent cycle stability and ion electro‐sorption and storage properties. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>